Some Geometric Properties for an Extended Class Involving Holomorphic Functions Defined by Fractional Calculus - Hussein, Sattar Kamil; Jassim, Kassim Abdulhameed (Iraqi Journal of Science, 2020)
The main objective of" this paper is to study a subclass of holomrphic and univalent functions with negative coefficients in the open unit disk U= defined by Hadamard Product. We obtain coefficients estimates, distortion theorem , fractional derivatives, fractional integrals, and some results.